EKSISTENSI TARI RADDAT SUNGAI KUNYIT DALAM PADA KOMUNITAS SENI AMANTUBILLAH DI KABUPATEN MEMPAWAH - Vrinka Vizura; Ismunandar Ismunandar; Asfar Muniir (Universitas Tanjungpura, 2019)
AbstractThis research aimed to determine the objective clarity about the existence or presence of Raddat Dance Sungai Kunyit Dalam in the Amantubillah art community at Mempawah district, West Kalimantan. The research method was a descriptive method in a qualitative form, through an ethnographic approach. The research data were obtained through several techniques, including observation technique, interview technique, and documentation technique. The research subjects were statements from the actors in Amantubillah art community. The research instrument was the researcher. In testing the validity of the data, the researcher did an extension of observations technique and also source triangulation technique that combines statements from sources. The result of this research was within the existence of Raddat Dance Sungai Kunyit Dalam in the Amantubillah art community at Mempawah District, West Kalimantan there were supporting factors such as the existence of Amantubillah art community, society needs and also the government support. Meanwhile factors that can obstruct the existence include the dancer of Raddat Dance Sungai Kunyit Dalam, the lack of government support and also in science and technology. It is hoped that the results of this research can be implemented in the lesson of Arts and Culture at grade X in odd semester. Keywords: Amantubillah Art Community. Existence, Raddat Dance Sungai Kunyit Dalam